New coumarin from the roots of Prangos pabularia. Issue 19 (2nd October 2018) - Numonov, Sodik; Bobakulov, Khayrulla; Numonova, Mukhabbat; Sharopov, Farukh; Setzer, William N.; Khalilov, Qosimjon; Begmatov, Nurmirza; Habasi, Maidina; Aisa, Haji Akber
Abstract: The new coumarin1, yuganin A (7-methoxy-8-((1 S, 2 S )-1, 2, 3-trihydroxy-3-methylbutyl)-2 H -chromen-2-one) along with nine known coumarins, heraclenol 3′- O -β-D-glucopyranoside (2 ), oxypeucedanin hydrate 3′- O -β-D-glucopyranoside (3 ), heraclenol (4 ), oxypeucedanin hydrate (5 ), osthole (6 ), oxypeucedanin (7 ), heraclenin (8 ), isoimperatorin (9 ), imperatorin (10 ) and the disaccharide sucrose (11 ), have been isolated from the roots of Prangos pabularia, and the structures of these isolated compounds were elucidated by spectroscopic means, especially, UV, HR-ESIMS, and 1D and 2D NMR spectroscopy. Furthermore, the anti-melanogenic effect of yuganin A and its inhibitory effect on B16 cells were evaluated. Yuganin A may be useful in the treatment of hyperpigmentation and as a skin-whitening agent in the cosmetics industry. Abstract :